Idea management canvas: big picture of web-based idea management models - Mikelsone, Elina; Segers, Jean-Pierre (Business: Theory and Practice, 2022)
Idea management process speeds up the innovation process by providing a systematic and manageable way of generating ideas vital to continues improvement and development within an organisation. There are many web-based tools that can support organisations with their idea management process. Based on the reviewed literature, currently there is no general model in literature that would support organisations in their idea management process based on the context. In this paper, authors describe the different idea management models based on the canvas model to account for the multidimensional context of web-based idea management systems. In prior research, authors have explored and identified the different idea management systems application types based on the different idea management systems classification types developed from the traditional business model canvas model. In this research, authors answer the following questions: What classifications based on the business model canvas could be created for idea management systems application, and how do these types manifest in real life? It is question that is identified a differences in the results, but form practical perspective understanding of different types could help for enterprises to choose the most appropriate one, but for IMS developers to enrich the types of IMS they are creating. In the literature there is only few attempt to classify IMS. Authors use the following research methods: a literature review (data collection: systematic data collection from scientific databases; data analysis: content analysis). Case study comprising data from over 100 enterprises with web-based idea management systems experience (data collection: case studies; data analysis: content analysis). To verify results 10 expert interviews were conducted. As a result, this research unlocks new value for idea management systems users and developers, as it shows the different idea management systems application types based on a specific business model canvas aspect. This resulted in the creation of 9 idea management systems classifications.